Analisis Pengaruh Kualitas Produk, Harga, Promosi Terhadap Keputusan Pembelian Di Rumah Makan Spesial Sambal Gonilan - Yunianto, Dody Ridwan; , Edi Purwo Saputro, S.E., M.Si (2016)
This research was conducted in Eating Special Sambal Gonilan, with the purpose of examining and analyzing the influence of the quality of products on purchase decisions in Eating Special Sambal Gonilan, test and analyze the effect of price on purchase decisions in Eating Special Sambal Gonilan and test and analyze the quality of the product, price and promotion on purchase decisions in Eating Special Sambal Gonilan. This study used a sample of 100 respondents, the method of data collection using the questionnaire. Analysis tools used are: testing instruments of data (validity and reliability testing), classical assumption (normality test, multicollinearity and heteroscedasticity test) and test hypotheses (multiple linear regression analysis, test the coefficient of determination (R2), F test and test t). The results of data analysis can be obtained as follows: Based on t test result calculation that all the independent variables consist of product quality, price and promotion influence on purchase decisions as evidenced by the value of tcount greater than the value t table then Ho is rejected means partially product quality, price and promotions significantly influence purchasing decisions.